2021
DOI: 10.1186/s13098-021-00629-4
|View full text |Cite
|
Sign up to set email alerts
|

A nutrient pattern characterized by vitamin A, C, B6, potassium, and fructose is associated with reduced risk of insulin‐related disorders: A prospective study among participants of Tehran lipid and glucose study

Abstract: Background Insulin-related disorders, including insulin resistance, insulin insensitivity, and insulinemia, is considered early predictors of major chronic disease risk. Using a set of correlated nutrient as nutrient patterns to explore the diet-disease relationship has drawn more attention recently. We aimed to investigate the association of nutrient patterns and insulin markers’ changes prospectively among adults who participated in the Tehran Lipid and Glucose Study (TLGS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 52 publications
(58 reference statements)
1
14
1
Order By: Relevance
“…Our study is the first case-control study investigating the association between NPs and NAFLD. A study most in line with our results relates to a prospective study that extracted an NP including vitamin A, vitamin C, pyridoxine, potassium, and fructose, and this pattern has been associated with a lower risk of hyperinsulinemia and IR, and dyslipidemia among participants from Tehran ( 22 , 23 ). Although there are considerable differences between this study and others in TLGS (Tehran lipid and glucose study), such as different study design, sample size, and outcome of the studies, based on the literature reviews, there is a significant correlation between hyperinsulinemia and IR with NAFLD ( 12 ).…”
Section: Discussionsupporting
confidence: 85%
“…Our study is the first case-control study investigating the association between NPs and NAFLD. A study most in line with our results relates to a prospective study that extracted an NP including vitamin A, vitamin C, pyridoxine, potassium, and fructose, and this pattern has been associated with a lower risk of hyperinsulinemia and IR, and dyslipidemia among participants from Tehran ( 22 , 23 ). Although there are considerable differences between this study and others in TLGS (Tehran lipid and glucose study), such as different study design, sample size, and outcome of the studies, based on the literature reviews, there is a significant correlation between hyperinsulinemia and IR with NAFLD ( 12 ).…”
Section: Discussionsupporting
confidence: 85%
“…Salehi-Abargouei et al [ 23 ] found three major nutrient patterns in a sample of Iranian adults. In another study by Teymoori et al [ 22 ] five major nutrient patterns were also found which were different from patterns obtained in our study. However, it should be keep in mind that since nutrient patterns are extracted from data obtained in the studied population with different dietary habits, consequently it is not expected that the nutrient patterns would be completely in accordance with each other.…”
Section: Discussioncontrasting
confidence: 99%
“…Few studies have evaluated the association between nutrient patterns and chronic diseases using factor analysis and provided different results in different populations [ 22 24 ]. In a recent published study from Iran, Teymoori et al [ 22 ] has reported that a nutrient pattern rich in dietary potassium, vitamins C and A, B 6 , and fructose was related to a lower risk of hyperinsulinemia, and insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic potassium deficiency is characterized by muscle weakness and acne or dry skin. These symptoms may progress to nervous disorders, decreased or irregular heartbeat and eventually could lead to loss of gastrointestinal tone if left untreated ( Teymoori et al, 2021 ). Cardiac arrhythmia is one of the most serious complications that happen in severe cases due to the sudden loss of potassium.…”
Section: Resultsmentioning
confidence: 99%